Small-Group Discussion Sessions on Imposter Syndrome - Natalie Baumann (Association of American Medical Colleges, 2020)
Introduction The Accreditation Council for Graduate Medical Education requires residency programs to support residents' well-being via established policies and programs. Imposter syndrome has been linked to burnout in residents, and understanding how to combat it may help improve resiliency in residents. Methods We held a facilitator-guided, interactive discussion session for internal medicine residents on the topic of imposter syndrome as part of a larger series of discussion sessions on resident wellness. We repeated the session to capture a different group of residents. A psychologist or chief resident led each 30- to 45-minute session with the option to include an attending physician. Residents, faculty, and a clinical psychologist developed instructions for leading this session. At the end of each session, the facilitator provided attendees with a handout with take-home points and an optional postsurvey to assess learning objectives and ask whether they felt this was an effective intervention to promote resident wellness. Results We collected data from 21 residents who attended the small-group discussion sessions. Ninety-six percent of residents felt comfortable recognizing imposter syndrome in themselves, and 62% knew the appropriate next steps after identifying imposter syndrome. Eighty-one percent of residents felt that the imposter syndrome wellness session was an effective intervention to promote resident wellness. Discussion Imposter syndrome has been linked to resident burnout, and discussing imposter syndrome was viewed as an effective intervention to promote resident wellness and resiliency. When creating wellness interventions, other programs should consider addressing imposter syndrome.